2017
DOI: 10.1115/1.4037981
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Trailing-Edge Serrations to Reduce Open-Rotor Tonal Interaction Noise

Abstract: A major source of contra-rotating open rotor (CROR) tonal noise is caused by the interaction of the front-rotor (FR) wakes with the aft-rotor blades. Inspired by chevron nozzles, which increase the mixing process in jet shear layers, serrations are implemented at the FR trailing-edge in order to increase the wake mixing and thus reduce the tones. The depth and width of the serrations are optimized with a multi-objective, metamodel-assisted evolutionary algorithm. For each member, a steady-state Reynolds-averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This lower than expected reduction was attributed to the dominance of the tip vortex interaction clouding any reduction due to serrations. Jaron et al [3] revisited the concept using an evolutionary algorithm to optimise the serration design. Jaron et al identified a maximum noise reduction of 1 dB from the optimisation of the serrations.…”
Section: Introductionmentioning
confidence: 99%
“…This lower than expected reduction was attributed to the dominance of the tip vortex interaction clouding any reduction due to serrations. Jaron et al [3] revisited the concept using an evolutionary algorithm to optimise the serration design. Jaron et al identified a maximum noise reduction of 1 dB from the optimisation of the serrations.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study is accompanied by calculations with an analytical fan noise prediction method. 3 In previous studies, this method has been used for acoustic optimization in the design process of turbofans [4][5][6] and helped to derive noise reduction measures. 7 In the present paper, the analytical method is used to help analyze the measured sound radiation upstream of an existing model fan.…”
Section: Introductionmentioning
confidence: 99%
“…Simplifying the physical model would greatly speed up the evaluation process (Elfert et al, 2017;Meyer, Daroczy, & Thevenin, 2017). Periodic assumptions were also generally used in CFD-O design process (Jaron, Moreau, Guerin, & Schnell, 2018;Kragic, Vucina, & Milas, 2018;Kragic, Vucina, & Milas, 2016). The application of appropriate approximation would lead to a drastic reduction of CFD evaluations (Bamberger & Carolus, 2017;Bargiel, Kostowski, Klimanek, & Gorny, 2017;Liang, Cheng, Li, & Xiang, 2011).…”
Section: Introductionmentioning
confidence: 99%